2005
DOI: 10.5424/sjar/2005032-149
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Nitrate reductase activity in roots and leaves of chickpea cultivars under salt stress

Abstract: Four chickpea cultivars (CSG 9651, BG 267, CSG 8962 and DCP 92-3) were grown to maturity under salinity conditions of 0, 4, 6 and 8 dS mE-1. Nitrate reductase activity decreased progressively with increasing salinity, although variation was seen between the cultivars. Cultivar CSG 9651, a kabuli or Mediterranean type, appeared to be the best adapted to saline stress, maintaining growth and showing efficient nitrate reduction under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
4
3
0
Order By: Relevance
“…Many factors influence how salt affects NR activity including plant species, nitrogen supply availability, salt content, and time duration of stress exposure to plants. Like present observation, exposure to increasing levels of NaCl significantly decreased the activity of NR in roots and leaf tissues of various agriculturally important vegetable crops including Solanum lycopersicum L. (tomato), Cucumis sativus L. (cucumber), 49 Zea mays L. (maize), 50 Beta vulgaris L. (sugar beet), 51 V. radiata L. (green gram), 52 Cicer arietinum L. (chickpea), 53 etc.…”
Section: Resultssupporting
confidence: 79%
“…Many factors influence how salt affects NR activity including plant species, nitrogen supply availability, salt content, and time duration of stress exposure to plants. Like present observation, exposure to increasing levels of NaCl significantly decreased the activity of NR in roots and leaf tissues of various agriculturally important vegetable crops including Solanum lycopersicum L. (tomato), Cucumis sativus L. (cucumber), 49 Zea mays L. (maize), 50 Beta vulgaris L. (sugar beet), 51 V. radiata L. (green gram), 52 Cicer arietinum L. (chickpea), 53 etc.…”
Section: Resultssupporting
confidence: 79%
“…Nitrate reductase enzyme is substrate inducible enzyme, its' induction is closely dependent on the availability of nitrate and the enzyme is found in cytosol of plant cells in leaves. The results are in close agreement with Garg and Singla (2005) who reported that nitrate reductase activity in the leaves in the chickpea cultivars decreased however maximum activity of this enzyme was observed after 70 days after sowing. Similar trend were also observed in the present investigation.…”
Section: Resultssupporting
confidence: 82%
“…NR and NiR enzymes are sensitive to alkalinity and their activities decreased with increasing level of alkalinity in the soil. The results are in close agreement with Garg and Singla (2005). Nitrogenase activity generally increased with plant age or decreased at flowering stage (Bidlack et al, 2001).…”
Section: Resultssupporting
confidence: 80%
“…Plant nitrogen conditions were no different in the various clones tested. In research Garg and Singla (2005), there was a decrease in NRA under saline conditions causing the degradation of nitrate reductase or decreasing in enzymes synthesis rate. NRA reduction in leaf and root occurred proportionally to the reduction of the dry weight root and shoot accumulation.…”
Section: Discussionmentioning
confidence: 99%